Polvilho Azedo: propriedades tecnológicas de produtos comerciais - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
Cassava starch stands out for its technological properties and it is widely used by industry. The native starch naturally fermented and sundried reach expansion properties, desirable for biscuits and cheese bread making. Another way to produce this product, with higher standardization, is by chemical modification. Both production methods are not regulated by the Brazilian legislation. Therefore, the aim of this work is to comprehend the technological properties of the product known as “polvilho azedo”. For this, eight commercial samples of sour cassava starch were analyzed to quantify the expansion index, organic acid content, titratable total acidity, amylose content, solubility and swelling power, syneresis and pasting and thermal properties. Morphology, X-ray diffraction, FTIR spectroscopy and rheology analyses were also carried out, always using a sample of native cassava starch for comparison. Significant difference was found for expansion, organic acids and rheology. Finally, through the results obtained, the eight samples were tentatively classified into two groups: modified starches obtained from oxidation process and naturally fermented starches with variations in intensity / type of radiation exposure.
Keywords: Modificação química; Reologia; FTIR; Fermentação natural; Propriedades térmicas; Chemical modification; Rheology; FTIR; Natural fermentation; Thermal properties; CNPQ::CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS